STRATEGI DALAM MEMPERTAHANKAN KESEHATAN MENTAL DARI CYBERBULLYING DI ERA DIGITAL PADA REMAJA - Salsabilla Ananda; Surawan (CV. Adiba Aisha Amira, 2025)
Cyberbullying is a form of digital violence that has a serious impact on adolescent mental health. In the digital era, adolescents are a vulnerable group due to the high intensity of social media use. This study aims to determine how positive comments on social media can function as a strategy in maintaining the mental health of adolescents who are victims of cyberbullying. This study uses a qualitative approach with content analysis. Data were obtained from comments on social media posts that display cases of cyberbullying, then analyzed to identify the forms of emotional support that emerged. The results showed that positive comments play an important role in providing empathetic support and strengthening self-esteem to victims. Empathetic support helps victims feel heard and not alone, while strengthening self-esteem can restore self-confidence and positive perceptions of themselves. Thus, positive comments have proven to be a simple but effective strategy in reducing the psychological impact of cyberbullying. These findings emphasize the importance of building a supportive and empathetic digital space for adolescent mental health.